Decision Support System for Selecting Outstanding Students Using a Combination of AHP and SAW Methods - Lira Uswatun Hasanah; Muhammad Fauzi Zulkarnaen; Maulana Ashari (Institute of Computer Science (IOCS), 2026)
The process of selecting outstanding students at MA Badrul Islam Gulung is still done conventionally, mainly by considering report card grades as the key factor, which could lead to subjectivity and be less effective in decision making. This study aims to develop a decision support system for selecting outstanding students using a combination of the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods. AHP is used to determine the priority weight of each criterion, while SAW is used to rank students based on preference scores. Data was collected through observation, interviews, questionnaires, and literature studies, involving 10 respondents and 5 student alternatives as research subjects. This study uses six assessment criteria: academic grades, non-academic achievements, behavior, discipline, activeness, and memorization of the Qur’an. The research results show that the combination of the AHP and SAW methods can produce a more objective, transparent, and systematic evaluation process. Based on the calculations, alternative A3, named Oktaviana, scored the highest at 0.991 and was chosen as the outstanding student because she had excellent and consistent scores across almost all assessment criteria, especially in academic performance, behavior, and Qur'an memorization. Thus, the decision support system that was developed can help the school determine outstanding students more accurately and efficiently